Cystathionine beta-Synthase (CBS) Domain-containing Pyrophosphatase as a Target for Diadenosine Polyphosphates in Bacteria - Viktor A. Anashkin; Anu Salminen; Heidi K. Tuominen; Victor N. Orlov; Reijo Lahti; Alexander A. Baykov (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2022)
Among numerous proteins containing pairs of regulatory cystathionine beta-synthase (CBS) domains, family II pyrophosphatases (CBS-PPases) are unique in that they generally contain an additional DRTGG domain between the CBS domains. Adenine nucleotides bind to the CBS domains in CBS-PPases in a positively cooperative manner, resulting in enzyme inhibition (AMP or ADP) or activation (ATP). Here we show that linear P-1,P-n-diadenosine 5'-polyphosphates (Ap(n)As, where n is the number of phosphate residues) bind with nanomolar affinity to DRTGG domain-containing CBS-PPases of Desulfitobacterium hafniense, Clostridium novyi, and Clostridium perfringens and increase their activity up to 30-, 5-, and 7-fold, respectively. Ap(4)A, Ap(5)A, and Ap(6)A bound noncooperatively and with similarly high affinities to CBS-PPases, whereas Ap(3)A bound in a positively cooperative manner and with lower affinity, like mononucleotides. All Ap(n)As abolished kinetic cooperativity (non-Michaelian behavior) of CBS-PPases. The enthalpy change and binding stoichiometry, as determined by isothermal calorimetry, were similar to 10 kcal/mol nucleotide and 1 mol/mol enzyme dimer for Ap(4)A and Ap(5)A but 5.5 kcal/mol and 2 mol/mol for Ap(3)A, AMP, ADP, and ATP, suggesting different binding modes for the two nucleotide groups. In contrast, Eggerthella lenta and Moorella thermoacetica CBS-PPases, which contain noDRTGG domain, were not affected by Ap(n)As and showed no enthalpy change, indicating the importance of the DTRGG domain for Ap(n)A binding. These findings suggest that Ap(n)As can control CBS-PPase activity and hence affect pyrophosphate level and biosynthetic activity in bacteria.